The Concept of Democracy Education as an Effort for Developing The Political Culture of Participating Communities - Randiawan, R.; Suryadi, Karim; Nur, Muhammad (International Journal Pedagogy of Social Studies, 2023)
Overcoming the concept of democratic education as an effort to develop the political culture of a participating society. This research was conducted using the method of library research (library research) by collecting information from various sources, such as books, journals with a qualitative approach. The results of the study show that the ideal concept of democratic education consists of three processes, first is the existence of political literacy for the community, second is the socialization of democracy through group discussion forums (FGD), public discussion of the community. The third is to provide political experience to the people by forming a democratic community. This political experience can be carried out through political parties, social organizations, and communities to support the direct involvement of the people in the democratic process. And forming a democratic culture of a participating society is the main agenda in the process of maturing democracy.